Community preparedness actions on cerebrovascular disease and variation of weather and climate - Alonso Freyre, Jorge Luis (2023)
Cerebrovascular disease is a neurological emergency that requires immediate diagnosis and therapeutic intervention, sometimes influenced by changes in weather and climate. The objective of the research was to carry out community preparation actions on cerebrovascular disease and the variation of weather and climate, through identifying the level of knowledge of family members, exposing a training program in relation to its results and evaluating the process carried out. A prospective multistage study was carried out at the "Mártires del 9 de Abril" University Hospital in Sagua la Grande, Cuba, between, 1993-2017. 100 relatives were selected for each stage. The collection of information was carried out through a survey of family members. The first stage the level of knowledge was moderately adequate in 63% of the relatives, the second stage predominated adequate in 48% of the respondents and in the third stage 61% have adequate knowledge. Actions such as the community health preparation plan were designed and implemented. It is evaluated in the reduction in the arrival of patients to the hospital, in the third stage, with a reduction in mortality from this disease. It is concluded that the community preparation actions on cerebrovascular disease and the variation of time and climate based on the training program, contributed to the elevation of the level of knowledge, reduction of waiting time and with it the reduction of mortality in this sickness.